2022
DOI: 10.1007/s10120-022-01357-y
|View full text |Cite
|
Sign up to set email alerts
|

CD44v3 is a marker of invasive cancer stem cells driving metastasis in gastric carcinoma

Abstract: Background Cancer stem cells (CSCs) are at the origin of tumour initiation and progression in gastric adenocarcinoma (GC). However, markers of metastasis-initiating cells remain unidentified in GC. In this study, we characterized CD44 variants expressed in GC and evaluated the tumorigenic and metastatic properties of CD44v3+ cells and their clinical significance in GC patients. Methods Using GC cell lines and patient-derived xenografts, we evaluated CD44+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…It is very likely that they regulate the same genes by forming the same SWI/SNF complex. Among them, we found that CD44 might be a good candidate since the latter was a well-known target of the SWI/SNF complex [ 28 ] and a proven marker of gastric cancer stem cells (GCSCs) [ 29 , 30 ], associated with proliferation of gastric epithelial cells [ 31 ]. Furthermore, CD44 was also known to be closely related to cell invasiveness and poor prognosis of GC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is very likely that they regulate the same genes by forming the same SWI/SNF complex. Among them, we found that CD44 might be a good candidate since the latter was a well-known target of the SWI/SNF complex [ 28 ] and a proven marker of gastric cancer stem cells (GCSCs) [ 29 , 30 ], associated with proliferation of gastric epithelial cells [ 31 ]. Furthermore, CD44 was also known to be closely related to cell invasiveness and poor prognosis of GC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD44 plays a crucial role in the resistance of CSCs to conventional therapies since it interacts with various components of the cell microenvironment, affecting cell adhesion, migration, and signaling pathways (167,169). Recent research has discovered that CD44v3 could be used as a marker of invasive cancer stem cells driving metastasis in gastric carcinoma (170). CD133 plays a pivotal role in the self-renewal capability of CSCs which maintaining their population within the tumor (171).…”
Section: Cd24 and Nkg2d Receptormentioning
confidence: 99%
“…Similarly, a meta-analysis assessing the prognostic significance of cancer stem cell markers in ovarian cancer from 52 studies concluded that CD44 correlated with worse disease-free survival, as well as with chemotherapy resistance [62].…”
Section: Expression Of Cd44 As a Prognostic Biomarkermentioning
confidence: 99%